El amor en el cine egipcio. Análisis de la relación hombre-mujer en algunas películas egipcias desde 1950 hasta 2000 - Melanie Croubalian (Universitat de Barcelona, 2001)
Love has always played a central role in Arab cultures, whether idealized/Platonic (as in the story of Majnûn and Laylâ) or earthly/carnal (as in the well-known Dove Ring. About Affinity and Friends by Ibn Hazm al-Andalûsî [993-1064]). Today love is still dealt with by many Arab philosophers and poets, especially Egyptian. This article intends to show the ways in which love has been represented in Egyptian cinema during the last fifty years, through four different categories of love: physical love, Platonic love, fatherly love and love between husband and wife. This essay demonstrates that contemporary Egypt’s conceptions of love are still very much the same as in the classical era, though contemporary cinema adds the support of the moving image to our understanding of this feeling.